Probing an Ixodes ricinus salivary gland yeast surface display with tick-exposed human sera to identify novel candidates for an anti-tick vaccine - Jos J. A. Trentelman (Nature Portfolio, 2021)
Abstract In Europe, Ixodes ricinus is the most important vector of human infectious diseases, most notably Lyme borreliosis and tick-borne encephalitis virus. Multiple non-natural hosts of I. ricinus have shown to develop immunity after repeated tick bites. Tick immunity has also been shown to impair B. burgdorferi transmission. Most interestingly, multiple tick bites reduced the likelihood of contracting Lyme borreliosis in humans. A vaccine that mimics tick immunity could therefore potentially prevent Lyme borreliosis in humans. A yeast surface display library (YSD) of nymphal I. ricinus salivary gland genes expressed at 24, 48 and 72 h into tick feeding was constructed and probed with antibodies from humans repeatedly bitten by ticks, identifying twelve immunoreactive tick salivary gland proteins (TSGPs). From these, three proteins were selected for vaccination studies. An exploratory vaccination study in cattle showed an anti-tick effect when all three antigens were combined. However, immunization of rabbits did not provide equivalent levels of protection. Our results show that YSD is a powerful tool to identify immunodominant antigens in humans exposed to tick bites, yet vaccination with the three selected TSGPs did not provide protection in the present form. Future efforts will focus on exploring the biological functions of these proteins, consider alternative systems for recombinant protein generation and vaccination platforms and assess the potential of the other identified immunogenic TSGPs.